Simultaneous quantification of six phenylethanoid glycosides in some Turkish Scutellaria species by a new HPLC-DAD method - Bardakci, Hilal; Acar, Ebru Turkoz; Kirmizibekmez, Hasan (TAYLOR \& FRANCIS LTD, 2019)
A new HPLC-DAD method was developed and validated for simultaneous determination of six main phenylethanoid glycosides (calceolarioside D, neocalceolarioside D, verbascoside, isoverbascoside, leucoseptoside A and martynoside) in the aerial parts of four Scutellaria L. taxa from flora of Turkey. All standard compounds showed a good linearity (R-2 > 0.999) in a relatively wide concentration range (1-120 mu g/mL). The LOD of the compounds was in the range of 0.104-1.295 mu g/mL and the LOQ was in the range of 0.450-2.536 mu g/mL. The recoveries of the selected compounds were calculated in the range of 97.46-117.85\%. The amounts of the phenylethanoid glycosides showed variation in the extracts. The developed method was found to be accurate, precise and reproducible, and successfully applied to identify and quantify the phenylethanoid glycoside composition of Scutellaria species. {[}GRAPHICS] .
Keywords: Scutellaria hastifolia; S; velenovskyi; S; albida ssp; albida; S; orientalis ssp; pinnatifida; HPLC-DAD; phenylethanoid glycosides